CHEMICAL PROPERTIES IN THE CONSERVATION AREAS OF GILIMANUK BAY, WEST COAST OF BALI - Muchtar, Muswerry (Marine Research in Indonesia, 2008)
The study on chemical properties in the conservation areas of Gilimanuk Bay, west coast of Bali was carried out in March 2006. The dissolved oxygen and degree of acidity (pH) in surface water were analyzed. The nutrients, consisting of phosphate, nitrate and ammonia concentrations in water were analyzed as well. In general all the chemical parameters were normal for coastal waters. Dissolved oxygen in this area was lower than those in Jakarta Bay and Panimbang waters, while the nutrient concentrations were lower compared to those of Cisadane Estuary, but higher compared to those of Mamberamo Waters. The fluctuations of pH, dissolved oxygen and other nutrients were influenced by the condition of surrounding area.